Перспективи паритетної демократії в Україні та завдання жіночого руху. - Демчук, Д.В.; Демчук, Д.В.; Demchuk, D. (Одеса, 2012)
The article is devoted to study and analysis of such global socio-political forms of participating in political sphere of society, as movements and pub- lic organizations, in particular, to research of types of woman movements. The different aspects of inﬂ uence of woman movements on forming of parity democracy in Ukraine are analysed.
Демчук Д.В. Перспективи паритетної демократії в Україні та завдання жіночого руху / Д.В.Демчук // Актуальні проблеми політики : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), М. А. Польовий (відп. секр.) [та ін.] ; НУ «ОЮА», Південноукр. центр гендер. проблем. – Одеса, 2012. – Вип. 47. – С. 99 - 107.
Keywords: Демократія в Україні; Жіночий рух; Політична сфера суспільства; Формування паритетної демократії в Україні; Формирование паритетной демократии в Украине; Политическая сфера общества; Женское движение; Демократия в Украине; Democracy in Ukraine; Women's movement; The political sphere of society; Formation of parity democracy in Ukraine